Algebra One

posted by .

Can I simplify this at all our expand it or something

-2(14x)+2(7x)
is it just really
-18x + 14 x
?

• Algebra One -

28x + 14x= 42x

Similar Questions

1. Inter. Algebra

what is the answer to 2 square root of 18x?
2. Algebra question

When you solve a system of equations by the substitution method, how do you determine whether the system of equations is dependent?
3. math

when I have (2x^(3)-18x)-(2x^(3)) / (x^(2)-9) am I suppose to be left with -18x/(x^(2)-9) or is it just 18x?
4. Math - Derivatives

Differentiate the given function. Simplify the answer. f(x) = 28x*ln√x + 42 f'(x) = 28*ln(x)^(1/2) + (1/(x^(1/2))*(1/2(x)^(-1/2)28x) f'(x) = 28*ln(x)^(1/2) + (14x*x^(-1/2))/x^(1/2) f'(x) = 28*ln(x)^(1/2) + (14x^(-1/2))/x^(1/2) …

6. Algebra

Is f(x) = 16 - 14x - 10x^2 - 19x^3 + 18x^4 a polynomial?
7. algebra

solve the following equation by clearing fractions show all work want to know if this right -7/3-5/2x=8+2x 6(-2/3)-(5/2x)(6)=6(8)+2x(6) 14x-15=48+12x 14x-12x-15=48+14x-14x 2x-15=48 2x-15+15=48+14x-14x 2x-15=48 2x-15+15=48+15 2x=-33 …
8. Chemistry

You know how when you do calculations for the enhaloy change of a reaction you start sort of like this?
9. Science (Chemistry)

Hello DrBob222 Regarding the answer you gave me thank you very much. However when you expand the denominator, I don't get -0.14 but I get -0.28. I get that because when I first expand I get 0.0049 - 0.14x - 0.14x + 4x^2. So when I …
10. Algebra

Really need some help 1. 14x^2+4+3x-12x^2-3+11x A) 2x^2+7x+1 B) 2x^2+14x+1 C) 2x^2+14x+7 D) 26x^2+7x+7 2. 4x^2+4-5x+x-2x^2+8 A) -2x^2+4x+12 B) -2x^2-4x+12 C) 2x^2+4x+12 D) 2x^2-4x+12

More Similar Questions